Substituent‐Guided Switch between CH Activation and Decarboxylative Cross‐Coupling during Palladium/Copper‐Catalyzed Cascade Reactions of 2‐Aminobenzoates with 2‐Haloarylaldehydes. Issue 32 (20th June 2013) - Bhowmik, Subhendu; Pandey, Garima; Batra, Sanjay
<x xml:space="preserve">Abstract</x> Cascade switch: Phenanthridines, pyrazole[4, 3‐c]quinolines and isocryptolepine were prepared in one step from the Pd/Cu‐catalyzed reaction between potassium 2‐aminobenzoates and 2‐haloarylaldehydes (see scheme). Although the reactions of 2‐aminobenzoates proceeded via a cascade imination/CH functionalization, the reactions of 6‐nitro‐2‐aminobenzoates ensued via a tandem imination/decarboxylative cross‐coupling.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>